'I want them better than me': Pedagogical strategies employed by four immigrant parents in the face of perceived forms of exclusion by school authorities. Issue 3 (3rd May 2016) - Markose, Susan Jacqueline; Simpson, Alyson
Abstract : In Australia, students from Chinese and Arabic language backgrounds form the largest minority language groups in the New South Wales (NSW) public school system. Yet the mainstream academic performance of students from these two communities show marked differences in their levels of attainment. This article explores the home literacy practices of two immigrant families – one from a Chinese background and the other of Lebanese heritage – in order to obtain insights into how parents support their children in the acquisition of mainstream literacies. It documents parents' perceptions of their interactions with school authorities in relation to their children's educational needs. Findings indicate that despite a plethora of inclusive policies adopted by the children's schools, the families in our study perceived school authorities as exclusionary in their practices. The article chronicles the sense of powerlessness and alienation experienced by both families when confronted with the rigidity of a school system they neither knew nor understood. Despite the similarities in their experiences, the Chinese family succeeded in the acquisition of mainstream literacies while the Lebanese family continues to struggle with the demands of the school curriculum. We present the contrasting solutions adopted by the two families to meet the educational needs of their children and indicate how their culturally derived responses go part way in explaining the different levels of school achievement experienced by the two families.